Laparoscopic herniorrhaphy in children - Mirko Bertozzi; Laura Marchesini; Simonetta Tesoro; Antonino Appignani (PAGEPress Publications, 2015)
The authors report their experience in laparoscopic repair of inguinal hernias in children. From May 2010 to November 2013, 122 patients with inguinal hernia underwent laparoscopic herniorrhaphy (92 males and 30 females). Telescope used was 5 mm, while trocars for the operative instruments were 3 or 2 mm. After introducing the camera at the umbilical level and trocars in triangulation, a 4-0 nonabsorbable monofilament suture was inserted directly through the abdominal wall. The internal inguinal ring was then closed by N or double N suture. All operations were performed in one-day surgery setting. In the case of association of inguinal and umbilical hernia an original technique was performed for positioning and fixing the umbilical trocar and for the primary closure of the abdominal wall defect. The postoperative follow-up consisted of outpatient visits at 1 week and 1, 3, and 6 months. The mean age of patients was 38.5 months. Of all patients, 26 were also suffering from umbilical hernia (19 males and 7 females). A total of 160 herniorrhaphies were performed; 84 were unilateral (66 inguinal hernia, 18 inguinal hernia associated with umbilical hernia), 38 bilateral (30 inguinal hernia, 8 inguinal hernia associated with umbilical hernia). Nine of 122 patients (6 males and 3 females) were operated in emergency for incarcerated hernia. A pre-operative diagnosis of unilateral inguinal hernia was performed in 106 cases. Of these patients, laparoscopy revealed a controlateral open internal inguinal ring in 22 cases (20.7%). The mean operative time was 29.9±15.9 min for the monolateral herniorrhaphies, while in case of bilateral repair the mean operative time was 41.5±10.4 min. The mean operative time for the repair of unilateral inguinal hernia associated with umbilical hernia was 30.1±7.4 while for the correction of bilateral inguinal hernia associated with umbilical hernia 39.5±10.6 min. There were 3 recurrences (1.8%): 2 cases in unilateral repair and 1 case a unilateral recurrence in a bilateral repair. No other complications were seen. Laparoscopic repair of inguinal hernia in children performed in this experience resulted a safe and effective procedure.